A systematic review of tests for lymph node status in primary endometrial cancer - Zamora Javier; Mann Christopher H; Selman Tara J; Khan Khalid S (BMC, 2008)
Abstract Background The lymph node status of a patient is a key determinate in staging, prognosis and adjuvant treatment of endometrial cancer. Despite this, the potential additional morbidity associated with lymphadenectomy makes its role controversial. This study systematically reviews the accuracy literature on sentinel node biopsy; ultra sound scanning, magnetic resonance imaging (MRI) and computer tomography (CT) for determining lymph node status in endometrial cancer. Methods Relevant articles were identified form MEDLINE (1966-2006), EMBASE (1980-2006), MEDION, the Cochrane library, hand searching of reference lists from primary articles and reviews, conference abstracts and contact with experts in the field. The review included 18 relevant primary studies (693 women). Data was extracted for study characteristics and quality. Bivariate random-effect model meta-analysis was used to estimate diagnostic accuracy of the various index tests. Results MRI (pooled positive LR 26.7, 95% CI 10.6 - 67.6 and negative LR 0.29 95% CI 0.17 - 0.49) and successful sentinel node biopsy (pooled positive LR 18.9 95% CI 6.7 - 53.2 and negative LR 0.22, 95% CI 0.1 - 0.48) were the most accurate tests. CT was not as accurate a test (pooled positive LR 3.8, 95% CI 2.0 - 7.3 and negative LR of 0.62, 95% CI 0.45 - 0.86. There was only one study that reported the use of ultrasound scanning. Conclusion MRI and sentinel node biopsy have shown similar diagnostic accuracy in confirming lymph node status among women with primary endometrial cancer than CT scanning, although the comparisons made are indirect and hence subject to bias. MRI should be used in preference, in light of the ASTEC trial, because of its non invasive nature.